P718 A Phase I Study of Ex Vivo Expanded Allogeneic Bone Marrow Derived Mesenchymal Stem Cells for the Treatment of Pediatric Perianal Fistulizing Crohn's Disease. (30th January 2023) - Otero Piñeiro, A; Lightner, A L; Reese, J; Ream, J; Nachand, D; Adams, A; VanDenBossche, A; Kurowski, J
Abstract: Background: Background: Mesenchymal stem cells have been used for the treatment of perianal Crohn's fistulizing disease by direction injection. However, no studies to date have included pediatric patients. Objective: To determine safety and efficacy of mesenchymal stem cells for pediatric perianal fistulizing Crohn's disease. Methods: Design: Phase I safety trial Settings: Tertiary inflammatory bowel disease referral center Patients: Crohn's patients aged 13-17 with perianal fistulizing disease. Intervention: 75 million mesenchymal stem cells were administered with a 22G needle by direct injection after curettage and primary closure of the fistula tract. A repeat injection of 75 million mesenchymal stem cells at 3 months was given if complete clinical and radiographic healing were not achieved. Main outcomes measures: Adverse and serious adverse events at post procedure day 1, week 2, week 6, month 3, month 6 and month 12. Clinical healing, radiographic healing per magnetic resonance imaging, and patient reported outcomes at the same time points. Results: Results: A total of 7 pediatric patients were enrolled and treated (6 male; median age of 16.7 years). There were no adverse or serious adverse events reported related to investigational product. At six months, 83% had complete clinical and radiographic healing. The perianal Crohn's disease activity index, Wexner incontinence score, and VanAssche score had all decreased at six months. Limitations: Single institution and open label. Conclusion: Bone marrow derived mesenchymal stem cells offer a safe, and likely effective, alternative treatment approach for pediatric perianal fistulizing Crohn's disease.